Delayed Influence of Spinal Cord Injury on the Amino Acids of NO• Metabolism in Rat Cerebral Cortex Is Attenuated by Thiamine - Boyko, Alexandra; Ksenofontov, Alexander; Ryabov, Sergey; Baratova, Lyudmila; Graf, Anastasia; Bunik, Victoria (Frontiers in Medicine, 2018)
Severe spinal cord injuries (SCI) result in chronic neuroinflammation in the brain, associated with the development of cognitive and behavioral impairments. Nitric oxide (NO•) is a gaseous messenger involved in neuronal signaling and inflammation, contributing to nitrosative stress under dysregulated production of reactive nitrogen species. In the present work, biochemical changes induced in the cerebral cortex of rats eight weeks after SCI, are assessed by quantification of the levels of amino acids participating in the NO• and glutathione metabolism. The contribution of the injury-induced neurodegeneration is revealed by comparison of the SCI- and laminectomy (LE)-subjected animals. Effects of the operative interventions are assessed by comparison of the operated (LE/SCI) and non-operated animals. Lower ratios of citrulline to arginine or citrulline to ornithine and a more profound decrease in the ratio of lysine to glycine distinguish SCI animals from those after LE. The data suggest decreased NO• production from both arginine and homoarginine in the cortex eight weeks after SCI. Both LE and SCI groups show a strong decrease in the level of cortex glutathione. The neurotropic, anti-inflammatory and antioxidant actions of thiamine (vitamin B1) prompted us to study the thiamine effects on the SCI-induced changes in the NO• and glutathione metabolism. A thiamine injection (400 mg/kg i.p.) within 24 hours after SCI abrogates the changes in the cerebral cortex amino acids related to NO•. Thiamine-induced normalization of the brain glutathione levels after LE and SCI may involve increased supply of glutamate for glutathione biosynthesis. Thus, thiamine protects from sequelae of SCI on NO•-related amino acids and glutathione in cerebral cortex.